2024
DOI: 10.26599/fshw.2022.9250025
|View full text |Cite
|
Sign up to set email alerts
|

Mogroside IIE,an in vivo metabolite of sweet agent,alleviates acute lung injury via Pla2g2a-EGFR inhibition

Abstract: In the face of increasingly serious environmental pollution, the health of human lung tissues is also facing serious threats. Mogroside ⅡE (M2E) is the main metabolite of sweetening agents mogrosides from the anti-tussive Chinese herbal Siraitia Grosvenori. The study elucidated the anti-inflammatory action and molecular mechanism of M2E against acute lung injury (ALI). A lipopolysaccharide (LPS)-induced ALI model was established in mice and MH-S cells were employed to explore the protective mechanism of M2E th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…In addition, clinical studies have found that sepsis-induced ALI can also be significantly attenuated through the effects of specific protein molecules including phospholipase A2 type IIA (Pla2g2a)-epidermal growth factor receptor (EGFR) [ 49 ], estrogen-related receptor alpha (ERRα) [ 50 , 51 ], mucin 1 (MUC1) [ 52 ], microRNA 199a (miR-199a) [ 53 , 54 ], gasdermin D (GSDMD) [ 55 , 56 ], tyrosine kinase with immunoglobulin, and epidermal growth factor homology domains 2(Tie2) [ 57 , 58 ]. These findings open new avenues for the development of therapeutic strategies for sepsis-induced ALI.…”
Section: Pathogenesis Of Sepsis-induced Ali and Potential Therapeutic...mentioning
confidence: 99%
“…In addition, clinical studies have found that sepsis-induced ALI can also be significantly attenuated through the effects of specific protein molecules including phospholipase A2 type IIA (Pla2g2a)-epidermal growth factor receptor (EGFR) [ 49 ], estrogen-related receptor alpha (ERRα) [ 50 , 51 ], mucin 1 (MUC1) [ 52 ], microRNA 199a (miR-199a) [ 53 , 54 ], gasdermin D (GSDMD) [ 55 , 56 ], tyrosine kinase with immunoglobulin, and epidermal growth factor homology domains 2(Tie2) [ 57 , 58 ]. These findings open new avenues for the development of therapeutic strategies for sepsis-induced ALI.…”
Section: Pathogenesis Of Sepsis-induced Ali and Potential Therapeutic...mentioning
confidence: 99%